The Relationship of Leadership Behavior of Heads of Nursing Divisions with the Organizational commitment of Nursing Staff. - علي, بشرى; ولاء هاشم اصبيره (Latakia University Journal -Medical Sciences Series, 2024)
The study aimed to study the relationship between the leadership behavior of nursing department heads and the organizational commitment of the nursing staff at Tishreen University Hospital. The sample consisted of (700) nurses working at Tishreen University Hospital, who were present during the study data collection and agreed to participate in it (the available sample was applied). The researcher used the Bosner & Kozes scale (2013) to measure the leadership behavior of nursing department heads from the nurses’ point of view, and a questionnaire to measure the level of organizational commitment, which the researcher Salman (2013) used in his evaluation of organizational commitment, to collect data related to the study, and after transcribing the data, it was processed statistically and tabulated using the program. SPSS version (21). the most important result of the study was: There is a relationship between the organizational commitment of the nursing staff and the leadership behavior of the heads of the nursing divisions, as the level of leadership behavior of the heads of the nursing divisions was average, and there is a statistically significant relationship between the leadership behavior of the heads of the nursing divisions, which is represented by supporting and enabling others to act, and the organizational commitment of the nursing staff to the degree Firstly, through encouragement, secondly, and through inspiring a shared vision In the third degree, while there is no statistically significant relationship between the leadership behavior of the heads of the nursing divisions represented by embodying the role model, challenging the methods of work and the organizational commitment of the nursing staff at Tishreen University Hospital, the level of standard commitment to organizational commitment was good, and both the level of emotional and continuous commitment was Average organizational commitment.